(3EjSGZhLjs - (3GdCHgQj GdSeQbfOj, CKjQ GdOjf, GdeaVd Hf YeQ GdeaVd, J (B663 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd CKjQ GdOjf GdCHgQj hHYO agPg QSGdI aj GdefWb ChQOfG ajgG eG jLH GSJMVGQgG def jHJOF GjSGZhLj GddaX GdOGd HGdhVY jOd Ydi JeGe eG hVY dg HGdeWGHbIs
(3BNQgG (B:s
(3hGdeZGdWI hgj bjGS eDda ef ebOeGJ cGPHI THjgI HGdMb hHGdeTghQI Ch ef ebOeGJ hgejI cGPHI hGdYeOI gh GdHQgGf dG ZjQ hdjcf gPG BNQ GdQSGdI aj GdefWbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/279s
(3eYLe GdeDdajf (B3/409s
(3cTa GdXfhf (B1/206s
(3gOjI GdYGQajf (B2/469s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs